Proposal for Labor Market Integration of Teachers in Contexts of High Social Vulnerability - Gutiérrez Gutiérrez, Magally (2011)
The purpose of this paper is to share a proposal for teacher’s labor market integration in contexts of high social5 vulnerability. This paper is the result of a research conducted in a priority attention primary school6 of the central canton of Heredia7. It explored the labor market integration process of teachers, considering the community, family and student reality of a population social risk. The research that supports this proposal is based on a qualitative approach, since the diagnosis process is not intended to provide answers that could be commonly applied to other education centers in similar contexts, but to make an exploratory approach of teachers’ reality and their integration process into education institutions of high social vulnerability. Therefore, although this paper intends to share this experience, it does not aim to unify integration practices, but to be an input in carrying out similar processes.   (5) The concept of high social vulnerability is understood based on Sojo’s approach (2003), which defines it as marginal urban communities in areas considered by the Costa Rican government as priority areas with the greatest social, economic backwardness in the country, and high rates of violence, leisure, unemployment and drug addiction. (6) Translator’s note: The Costa Rican education system is composed of primary education (1st-6th grade) and secondary education (7th-11th grade). (7)A public primary school in the circuit 02 of the Province of Heredia.